Development of a robotic hand glove system for secure grasp with AI wireless sensor data - Almassri, Ahmed; Koyanagi, Ken'ichi; Wada, Chikamune; Horio, Keiichi; Wan Hasan, Wan Zuha (IEEE, 2023)
Robotic Hand glove is one of the most commonly used technique in the rehabilitation systems. In this paper, we developed a robotic hand system with a proposed sensing mechanism-based AI algorithm, which can acquire grasping forces from human fingers. It is composed of five low-cost force sensors attached to the glove’s fingertips and wireless data logger. Several experiments including grasping a plastic bottle and squeezing a tennis ball are implemented to verify the efficiency of the proposed system using the developed glove. As a result, it accurately estimates the forces applied by each finger with the aim of achieving a secure grasp comparison with conventional methods.